PUSAT BARANG BEKAS LAYAK PAKAI DI KOTA BANJARBARU - Rahmatillah, Muhammad Baidi; Tharziansyah, Muhammad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The design of the Used Goods Center in Banjarbaru City was motivated by the increased production of waste in Banjarbaru City after the COVID-19 pandemic and the proliferation of secondhand shops selling illegally imported used goods. The problems faced are in the form of many used goods stores that provide an inadequate shopping experience so that they do not attract visitors. The design method used is the Architectural Program by managing information and then analyzing the design to produce the right design. The design concept uses a One Stop Shopping Experience which provides a complete shopping experience, starting from selling on a consignment system, buying, and trying used goods in one facility. The furniture design uses the concept of upcycling waste as a solution to reduce waste production in Banjarbaru City. The result of the design is an elongated two-story building surrounded by old window and door facades. The building area is 1875m2 facing north with two main functions, namely a used goods service center and a used goods shopping area.